On Promoting Fiscal Discipline in Thailand: Policy and Practical Recommendations - Boonkob, Panaikorn (วารสารสังคมศาสตร์บูรณาการ มหาวิทยาลัยมหิดล, 2022)
Fiscal discipline is one of the important concepts in fiscal policy areas. Fiscal discipline is referred to as having good fiscal monitoring process and management that can contribute to long-term fiscal stability and sustainability of the nation. Thus, governments should pay special attention to the notion of fiscal discipline when formulating and implementing fiscal policies or applying fiscal instrument to stimulate the economy of the nation. The objectives of this article were to analyze the economic paradigm of fiscal discipline measurements in Thailand and offer recommendations regarding the appropriate and suitable fiscal discipline measurements in the Thai context. Three recommendations to improve fiscal discipline in Thailand include focusing on 5 key aspects of fiscal discipline, using econometrics methodology, and applying institutional governance principles in the fiscal policies and practices.